AN EMPIRICAL STUDY ON INTERCULTURAL COMPETENCE OF CHINESE UNIVERSITY TEACHERS WORKING WITH BACHELOR-TRANSLATORS - Yanshi, Liu (Scientific Journal of Polonia University, 2023)
This article presents a factor-criterion model of determining the intercultural competence of Chinese university teachers who work with bachelor-translators. The practical result of the scientific research of the article is the system of recommendations to the management of the intercultural competence development of teachers who work with bachelor-translators in the condition of Chinese institutions of higher education. The article systematizes the main problems of improving the intercultural competence of teachers in Chinese institutions of higher education. The article considers the internal and external factors of developing intercultural teaching competence of teachers in Chinese institutions of higher education. The article emphasizes that the intercultural competence of the teacher, as a systematized set of knowledge, abilities and qualities that ensure the optimal implementation of pedagogical activities, is aimed at meeting both professional and social needs, is a multilevel system that develops over time from the three intercultural dimensions of emotion, cognition and skill. The essence of social and professional needs of teachers in the conditions of Chinese institutions of higher education is considered with the approaches of regular training and intercultural experience. The components of the model of determining the intercultural competence of the Chinese university teachers working with bachelor-transactors are analyzed and considered in detail. The article presents the essence of pedagogical conditions, which is necessary for designing the intercultural teaching training process in the conditions of Chinese institutions of higher education, and it contributes to the development of the intercultural competence of teachers in teaching implementation. The specifics of the pedagogical approach to the development of intercultural competence of Chinese university teachers are considered. The scientific result of the research was the proposed model of determining the intercultural competence of teachers in the conditions of Chinese institutions of higher education, which is verified to improve the intercultural competence of teachers who work with bachelor-translators.